2017
DOI: 10.15406/jdvar.2017.05.00151
|View full text |Cite
|
Sign up to set email alerts
|

Gross Morphological and Morphometric Studies of Oviduct in Three Genotypes of Nigerian Indigenous Laying Chickens

Abstract: Gross and morphometric studies were carried out on the oviducts of three Nigerian indigenous genotypes of chicken. Fifteen adult laying chickens of three genotypes {five female per genotype of Normal Feathered (NoF), Naked Neck (Na) and Frizzle Feathered (FF)} were bought from Mokwa local markets. They were quarantined for two weeks, stabilized for another week, live weights were taken and then slaughtered using Halal method. After careful evisceration, segments of oviduct were examined grossly and then weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…The current findings of oviduct which appeared to be long, less convoluted, highly vascular tube and occupied the most left side are similar to those recorded by Khokhlov and Kuznetcov (2007), Mahmud (2017). Similarly, Veterany and Jedlička (2002) reported that the oviduct of the hen was well-developed at the left side, atrophied at the right side and consisted of all five regions as described in the present study.…”
Section: Resultssupporting
confidence: 89%
“…The current findings of oviduct which appeared to be long, less convoluted, highly vascular tube and occupied the most left side are similar to those recorded by Khokhlov and Kuznetcov (2007), Mahmud (2017). Similarly, Veterany and Jedlička (2002) reported that the oviduct of the hen was well-developed at the left side, atrophied at the right side and consisted of all five regions as described in the present study.…”
Section: Resultssupporting
confidence: 89%
“…Infundibulum was the 1 st segment of the oviduct and it was funnel shaped in the upper portion and muscular tubular structure in lower portion which was similar with the findings of previous workers [1], [7]- [9], [12]. At 20-24 weeks of age, a narrow neck observed during the rapid development of infundibulum and not observed in lower age due to underdevelopment [11], [13].…”
Section: A Anatomysupporting
confidence: 87%
“…In case of deshi chicken the mean length of infundibulum was 7.18±4.22 cm at 8-11 months whereas at 5 months it was 5.85 cm [21]. The length, width and weight of infundibulum in three genotypes of Nigerian indigenous laying chickens varied considerably [7]. The mean values were 4.33±0.60 cm as length, 2.03±0.3 cm as width and 0.68±0.02 g as weight in Normal Feather (NOF); 6.53±1.89 cm as length, 2.17±0.16 cm as width and 0.8±0.15 g as weight in Naked Neck Feather (NEF); 6.4±0.70 cm as length, 2.67±0.33 cm as width and 0.77±0.27 gm in Frizzle Feather (FF).…”
Section: B Morphologymentioning
confidence: 94%
“…Higher values of the width of oviduct during breeding season and significantly decreased during non-breeding season as depicted in (table 1). In Nigerian indigenous laying chickens, the mean width of the oviduct was recorded as (1.07±0.07 cm) (Ma, 2017). The width of oviduct of rose ringed parakeet was lower than Nigerian indigenous laying chickens because lower body weight and size.…”
Section: Discussionmentioning
confidence: 89%